Gains associated with linking the EU and Chinese ETS under different assumptions on restrictions, allowance endowments, and international trade - Malte Winkler; Sonja Peterson; Sneha Thube (Kiel Institute for the World Economy (IfW), 2021)
Linking the EU and Chinese Emission Trading Systems (ETS) increases the cost-efficiency of reaching greenhouse gas mitigation targets, but both partners will benefit - if at all - to different degrees. Using the global computable-general equilibrium (CGE) model DART Kiel, we evaluate the effects of linking ETS in combination with 1) restricted allowances trading, 2) adjusted allowance endowments to compensate China, and 3) altered Armington elasticities when Nationally Determined Contribution (NDC) targets are met. We find that generally, both partners benefit from linking their respective trading systems. Yet, while the EU prefers full linking, China favors restricted allowance trading. Transfer payments through adjusted allowance endowments cannot sufficiently compensate China so as to make full linking as attractive as restricted trading. Gains associated with linking increase with higher Armington elasticities for China, but decrease for the EU. Overall, the EU and China favor differing options of linking ETS. Moreover, heterogeneous impacts across EU countries could cause dissent among EU regions, potentially increasing the difficulty of finding a linking solution favorable for all trading partners.
Keywords: F13; F18; Q58; Q54; 330; Paris Agreement; NDC; Emission Trading; Linking ETS; China; EU; Verbindung von Emissionshandelsystemen; NDC; Pariser Klimabakommen; Emissionshandel